Spinal anesthesia in infants undergoing urologic surgery duration greater than 60 minutes. Issue 6 (December 2022) - Jefferson, Francis A.; Findlay, Bridget L.; Handlogten, Kathryn S.; Gargollo, Patricio C.; Warner, Lindsay L.; Woodbury, Jason M.; Haile, Dawit T.; Granberg, Candace F.
Summary: Introduction: Spinal anesthesia (SA) has been safely utilized in infants. There are limited data regarding the safety and efficacy of SA in pediatric urologic surgery lasting ≥60 min. We outlined the perioperative course for infants undergoing single-injection 0.5% plain bupivacaine SA-only for urologic procedures lasting ≥60 min. Objective: To characterize the safety and efficacy of SA for urologic surgery in infants lasting ≥60 min. Methods: We reviewed our prospectively maintained database of infants undergoing SA for urologic procedures lasting ≥60 min from May 2018 to March 2021. Patients received preoperative intranasal dexmedetomidine, some received intranasal fentanyl, and all patients received lidocaine cream applied preoperatively over the lumbar spine. Oral sucrose on a pacifier was provided as needed, and the patient's arms were swaddled for the procedure. Success was defined as no conversion to general anesthesia. Time points for start/end of spinal injection, procedure duration, wheels in/out of operating room (OR), and discharge were collected. Results: Of 245 cases conducted with SA during the study period, 76 (31%) infants underwent surgery lasting ≥60 min. Of these, 73 (96%) were successfully completed with SA alone. In the 3 cases converted to general anesthesia, 2 (67%) required mask anesthesia after 96 and 169 min (for the last <10 min of surgery), and one was converted to intubation before start of surgery. Median patient age was 6 (IQR 5–7) months, and median procedure length was 95 (IQR 75–120) minutes. Following initial preoperative intranasal dexmedetomidine ± fentanyl, at least one additional dose of IV sedative was given in 27 (36%) cases at a median time of 90 (IQR 60–120) minutes into surgery. Following closure, patients exited the OR after a median 10 (IQR 8–12) minutes and subsequently discharged after spending a median of 73 (IQR 61–96) minutes in recovery. Discussion: We describe pediatric urologic surgical cases lasting ≥60 min that employed single-injection intrathecal bupivacaine alone without adjunct intrathecal agents. In this report, SA was safely utilized in infants undergoing urologic procedures lasting at least 60 min, with about 40% of patients receiving additional IV dexmedetomidine and fentanyl. Non-medication measures (swaddling, oral sucrose) were important for maximizing patient comfort. Communication between surgeon and anesthesia as cases progress is key to maintaining adequate anesthesia. Conclusion: A single-injection bupivacaine-only spinal anesthesia approach for urologic surgery lasting over an hour and up to 3 h is safe and effective in infants. Selecting appropriate candidates for SA should be a joint decision between the surgeon and the anesthesiologist. Summary Figure 1Obtaining spinal access in an infant prior to urologic surgery. Lidocaine 1% is injected into superficial skin over planned spinal access site (A). Spinal access is obtained (B), free flow of cerebrospinal fluid documented (C), and single-injection spinal anesthesia using 0.5% bupivacaine is administered (D). Summary figure